Telemedicine and Preventive Behaviors in Type 2 Diabetes: A Prolanis Study in Semarang, Indonesia - WULAN, WIDYA RATNA; Pantiawati, Ika; Widianawati, Evina; Wulandari, Fitria (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2026)
Background: Type 2 Diabetes Mellitus (T2DM) represents an increasing public health challenge in Indonesia, placing considerable pressure on the country healthcare infrastructure. The Prolanis program, a nationwide initiative for managing chronic diseases, incorporates telemedicine to encourage preventive practices among patients with T2DM. Objective: This research sought to investigate the relationship between knowledge, attitudes, and perceptions regarding telemedicine and preventive behaviors for T2DM among participants in the Prolanis program in Indonesia. Methods: A cross-sectional quantitative study was carried out involving 157 Prolanis participants (including 100 individuals diagnosed with T2DM) in Semarang. Data collection employed validated questionnaires designed to evaluate knowledge, attitudes, and perceptions of telemedicine in connection with T2DM preventive behaviors. Associations between these factors and preventive behaviors were analyzed using the Mann-Whitney test. Results: Approximately  47.1% of respondents demonstrated a good level of knowledge about T2DM. Attitudes toward telemedicine within the Prolanis program remained predominantly negative (59.0%), whereas 68.3% exhibited positive perceptions of telemedicine. No statistically significant associations were identified between knowledge (p=0.281), attitudes (p=0.162), or perceptions (p=0.229) of telemedicine and T2DM preventive behaviors among the participants. Conclusion: Knowledge, attitudes, and perceptions of telemedicine do not significantly affect preventive behaviors related to T2DM. These results indicate that existing telemedicine approaches in the Prolanis program may need improvement, potentially through customized educational efforts or improved user engagement strategies, to better support T2DM prevention.